Emotional Dysregulation and its Association with Non-Suicidal Self-Injury Among Nursing Students at Universitas Gadjah Mada - Nur Halimah, Faiha; Warsini, Sri; Setiyarini, Sri (Universitas Airlangga, 2025)
Introduction: College students often experience difficulties in managing their emotions effectively (emotional dysregulation), where individuals with high levels of emotional dysregulation tend to use non-suicidal self-injury (NSSI) as a form of emotional management and to cope with negative influences. Research on the relationship between emotional dysregulation and NSSI among nursing students has not been conducted. Method: This study is a correlational analytical study with a cross-sectional design. The study population consisted of nursing students of the Faculty of Medicine, Public Health, and Nursing of Universitas Gadjah Mada (FK-KMK UGM). From this population a sample of 130 students was obtained through convenient sampling because the topic raised was sensitive so that respondents could participate in this research without being known by anyone else except the researcher. To measure the emotional dysregulation and non-suicidal self-injury the instruments of Difficulties in Emotion Regulation Scale (DERS) and the Self-Harm Inventory (SHI) were used. Data analysis employed the Spearman Rank Correlation test. Results: Part of the nursing students (59.2%) of FK-KMK UGM experienced emotional dysregulation, but the majority (77.7%) did not engage in NSSI. Emotional dysregulation differed significantly only based on cohort, while NSSI did not show significant differences based on all respondent characteristics (age, gender, cohort, and residence). Correlation analysis of emotional dysregulation and NSSI yielded a correlation coefficient (r) of 0.496 with a significance value (p) of 0.001. Conclusions: There was a significant relationship with moderate strength and a positive direction between emotional dysregulation and NSSI among nursing students at FK-KMK UGM.